Aroma profiling of long shelf-life yoghurt from milk with varying acidity: Insights from sensory evaluation and instrumental analysis - Jia Wang; Dongjie Zhang; Jie Li; Tingting Zou; Rong Wen; Yaqiong Hou; Huanlu Song; Hongliang Li; Hairan Ma; Jiao Shi (Food Chemistry: X)
In this study, the aroma components of long shelf-life yoghurt produced from milk with varying acidity levels were identified using the Stir Bar Sorptive Extraction (SBSE) coupled with comprehensive two-dimensional gas chromatography−olfactometry−mass spectrometry technology (GC × GC-O-MS) for the first time. A total of 16 and 12 aroma-active compounds were characterized in long shelf-life yoghurt and milk, respectively, through qualitative analysis. Subsequent precise quantification and calculation of odor activity values (OAVs) showed significant differences in aroma profiles among samples with different compound concentrations. Finally, partial least squares-discriminant analysis (PLS-DA) and variable importance of projection (VIP) showed that the differential compounds in long shelf-life yoghurt were acetoin, butanoic acid, 2,3-butanedione, hexanoic acid, and nonanal, while the differential compounds in milk samples were hexanoic acid, 2,3-butanedione, decanal, nonanal, and acetic acid. These findings provide novel insights into the effect of milk acidity on the aroma components of long shelf-life yoghurt.